2018
DOI: 10.7567/apex.11.041301
|View full text |Cite
|
Sign up to set email alerts
|

Origin of room-temperature photoluminescence around C-line in electron-irradiated Si and its applicability for quantification of carbon

Abstract: We demonstrate that a broad emission band is observable at room temperature in the vicinity of the carbon-related C-line detected at cryogenic temperatures in electron-irradiated Si. Its spectral shape is different from similar shapes of the bands due to dislocations, oxygen precipitates, and thermal donors. The band is annealed out at 450 °C and its intensity ratio to the band-edge emission has a positive correlation with carbon concentration in the same manner as the C-line. We deduce that the band has a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 29 publications
(55 reference statements)
1
18
3
Order By: Relevance
“…[7] A broad emission with center energy 0.78 eV has in several studies been linked to carbon in bulk monocrystalline silicon materials. [20] However, this is not consistent with our recordings of this as a surface effect. As the low-signal strengths resulted in low Signal to noise ratio (S/N) ratio for spatial images, the unetched samples are not treated further here.…”
Section: Oxygen Measurementscontrasting
confidence: 81%
See 2 more Smart Citations
“…[7] A broad emission with center energy 0.78 eV has in several studies been linked to carbon in bulk monocrystalline silicon materials. [20] However, this is not consistent with our recordings of this as a surface effect. As the low-signal strengths resulted in low Signal to noise ratio (S/N) ratio for spatial images, the unetched samples are not treated further here.…”
Section: Oxygen Measurementscontrasting
confidence: 81%
“…Overview of the spectral emission lines found in Cz-Si exhibiting TDs. [18][19][20] Details of each of the emission lines are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects, such as oxygen precipitates and vacancy‐light element complexes, form due to the interaction between these impurities and point defects during device processes, such as ion implantation, so that they would degrade carrier lifetime and increase C–E leakage current and on‐voltage of IGBTs. It has recently been reported that carbon‐related complexes, such as Ci‐Cs (G‐line) and Ci‐Oi (C‐line), decrease lifetime . Therefore, reducing carbon in the crystal has been required.…”
Section: Comment On Development Of Mcz‐si Crystals For Future Siliconmentioning
confidence: 99%
“…It has recently been reported that carbonrelated complexes, such as Ci-Cs (G-line) and Ci-Oi (C-line), decrease lifetime. [57][58][59] Therefore, reducing carbon in the crystal has been required. In addition, because high-voltage IGBTs for infrastructure applications of a power supply require high resistivity and high lifetime materials, FZ-Si crystals with neutron transmutation doping (NTD) are used.…”
Section: Future Researchmentioning
confidence: 99%